Antibacterial Evaluation of Gradient Extracts of Adiantum latifolium Lam. Towards Pathogenic Cutaneous Bacteria - Toji Thomas (Journal of Global Pharma Technology, 2017)
Objective: The study focused to analyse antibacterial evaluation of gradient extracts of Adiantum latifolium, a healing pteridophyte towards bacteria involved in cutaneous infections. Methods: Whole plant of Adiantum latifolium was analyzed for its antibacterial nature and phytochemical components in different solvents extracts of accelerating polarity. Disc diffusion method was used to analyse antibacterial activity. Preliminary phytochemical evaluation was done using various spraying reagents. Minimum inhibitory concentration as well as minimum bactericidal concentration was determined towards Pseudomonas aeruginosa. Results: The plant primarily exhibited antibacterial activity in ethanol extract. Maximum intensity of activity was noticed towards Pseudomonas aeruginosa, a resistant strain towards amoxicillin and chloramphenicol. Petroleum ether and water extracts could not show any antibacterial activity towards the tested organisms. Flavonoids and phenols were found in different extracts. Occurrence of flavonoid and phenol in ethanol extract of the plant can be an explanation for its antibacterial activity. Ethanol extract of the plant showed minimum inhibitory concentration as 18.75mg/ml and minimum bactericidal concentration as 37.5mg/ml towards Pseudomonas aerogenosa. Conclusion: Adiantum latifolium showed antibacterial activity in ethanol extract especially towards Pseudomonas aeruginosa. Adiantum latifolium; Antibacterial activity; Phytochemical; Pteridophytes.